Assessment and Management of Hurricane Damaged Timberland - Alan Long; Jarek Nowak; Chris Demers; Rick Williams; Nicole Strong; Jib Davidson; John Holzaepfel (EDIS)
Every year, southern timberland is damaged by hurricanes, ice storms, or tornados somewhere in the region. In response, a variety of information sources have been developed to address the many issues associated with such damage. This fact sheet summarizes information and guidelines from these sources, with a focus on Florida. It provides guidance to forestland owners for assessing severe storm damage, handling salvage operations and timber sales, minimizing potential impacts of other disasters after the storm, dealing with financial issues such as income tax casualty losses, and altering management plans. The references listed at the end may provide landowners with additional information relevant to their particular situation (see Figure 1). This document SS-FOR 22, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published in January 2005.